An aspect of the Japanese language in relation to dyslexia : a thesis presented in partial fulfilment of the requirement for the degree of Master of Arts in Japanese at Massey University - Roberts, Joan Gladys (Massey University, 1987)
These studies were conducted to examine the processing of two kinds of Japanese orthography, namely, kanji and hiragana by a group of dyslexic Subjects and Subjects in a control group of similar age, in order to ascertain the effectiveness of hemispheric specialization. An analysis of variance showed that in visual-learning there was a significant main effect for script type for both groups, F(l,36), = 28.125, p < .001. There was also significance for the dyslexic group in verbal-recall, F(l,36), = 13.15, p < .001. There was a significant interaction between group and script for direction-orientation with kanji showing higher correct responses, F(l,36), = 4.142, p < .05. These results confirmed expectations based on research and also identified left brain (Right Hemisphere) strengths. Thus it seems that a much closer examination of learning styles and modes of learning is crucial for the dyslexic group. Japanese brain lateralization, seen to differ from Western lateralization, appears to be linked with environment which is closely related to language type. This study is an investigation from a culture-specific perspective with a consideration of neurolinguistics in cerebral hemispheric lateralization. This is considered in view of the existence of certain difficulties with regard to reading and the possible influence of life-style and familial career selections to which those difficulties might accrue.
Keywords: Japanese language; Dyslexia